(untitled) (Physical Education, Health and Social Sciences, 2025)
Objectives: To compare the lipid lowering efficacy of rosuvastatin and atorvastatin in high risk dyslipidemic patients. Study design: Randomized controlled trial Place and duration of study: Department of cardiology, PAEC General Hospital, Islamabad, from 1st of December 2023 to 31st of March 2024. Methods: A total of 230 high risk dyslipidemic patients above the age of 18 years reporting at out-patient department were added in this study. These patients were divided in to 2 equal groups where patients in Group R were given rosuvastatin 20 mg/day while patients in Group A were given Atorvastatin 20 mg/day for 8 weeks. Venous blood samples were arranged at the start and at the end of study with patients having at least 12 hours fasting. The efficacy of both the treatments were evaluated on the basis of effects on the total cholesterol (TC), low density lipoproteins cholesterol (LDL C), triglycerides (TG) and high density lipoprotein cholesterol (HDL C) levels. The percentage of patients achieving the target levels of TC and LDL C was also compared between the 2 groups. Results: The Mean±SD of age in this study was 55.54±8.05 years. After 8 weeks of treatment, the results showed a significantly decreased levels of TC (184.98±20.84 Vs 192.55±18.84, p=0.004) and LDL C (128.59±19.65 Vs 134.09±18.01, p=0.028) in Group R compared to Group A. Moreover, significantly more patients achieved the target levels of TC (64.34% Vs 50.43%, p=0.032) and LDL C (20.87% Vs 10.43%, p=0.029) in Group R compared to Group A. There were also decreased levels of TG and increased levels of HDL C in Group R compared to Group A, however, this difference was statistically non-significant. Conclusion: Rosuvastatin provides better lipid-lowering efficacy compared to atorvastatin in high risk dyslipidemic patients.